Using disaster recovery knowledge as a roadmap to community resilience. Issue 2 (15th March 2019) - Kirkpatrick, Sarah Jo Bundy
ABSTRACT: There remains a lack of consensus surrounding the definition of resilience in the disaster context. While scholarly endeavors to remedy this definitional deficiency are valuable, it is important that they do not overshadow the practical applicability of the concept. This article seeks to move beyond the dialog swirling around the definition of resilience by using the academic literature around a singular disaster recovery task – business recovery – to demonstrate how this literature can inform concrete community action related to the task. Specifically, the article outlines literature-based factors associated with improved recovery outcomes for businesses to illustrate how it is feasible to use this knowledge to not only predict business recovery in a community, but also to extrapolate how to assess and improve business recovery, as well as deduce actions that can be perhaps taken by communities pre-disaster to influence the post-disaster outcomes.